Assessment 100% Supported by ICT: Possibilities Offered and Risks - Teherán Sermeño, Plinio del Carmen; Almanza Montero, Ovidio Amado; Mendoza, Henry (International Journal of Emerging Technologies in Learning (iJET), 2010)
After the launching of a Fundamentals of Physics course offered for different campuses of the National University of Colombia in blended learning mode, various experiences were collected in a virtual assessment that were supported 100% by ICT. We implemented an evaluation system that consists of different categories ranging from traditional examinations, partial examinations, final examinations, workshops, quizzes, attendance, and duties and forums, all evaluated online. In particular, random blocks of questions were used for examinations taken from large databases, built especially for this purpose, on the order of 100 per chapter. We comment on the results achieved with the implementation of the evaluation system proposed, in addition to the possibilities offered and the risks they present.